2019
DOI: 10.1080/1045988x.2018.1534224
|View full text |Cite
|
Sign up to set email alerts
|

Schoolwide positive behavioral interventions and supports in an alternative education setting: Examining the risk and protective factors of responders and non-responders

Abstract: This research examined the risk and protective factors of responders and non-responders to a school-wide implementation of positive behavioral interventions and supports (SW-PBIS) within an alternative school. Students completed self-perception measures of individual, school, community, and home systems. Multivariate analysis of variance indicated a statistically significant difference between responders and non-responders on the individual and school systems models. Direct logistic regression indicated that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In the review of the research, having friendships with other students who shared the same expectations of academic continuity (Gamella, 2011; Griffiths et al, 2019) was found to be a protective factor. When asked in the questionnaire whether they considered the positive/equal relationship with classmates in primary and secondary school as a factor that had contributed to their academic trajectory, 73.4% said that this was the case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the review of the research, having friendships with other students who shared the same expectations of academic continuity (Gamella, 2011; Griffiths et al, 2019) was found to be a protective factor. When asked in the questionnaire whether they considered the positive/equal relationship with classmates in primary and secondary school as a factor that had contributed to their academic trajectory, 73.4% said that this was the case.…”
Section: Resultsmentioning
confidence: 99%
“…In the face of these barriers, and being aware that the continuity of school trajectories depends, to a large extent, on intervention policies and specific programmes (Abajo and Carrasco, 2004; Bereményi and Carrasco, 2015; Gamella, 2011), we find the need for protective factors for school success (Griffiths et al, 2019) in Roma students, which we define as the personal and social conditions that favourably influence Roma students’ access to, and continuity in, higher education. These factors cannot be understood in isolation, but rather their influence must be understood as intersecting – just as the causes of school dropout and exclusion are also intersecting (Vázquez, 2020) and ought to be seen from a processual and relational perspective – giving rise to particular trajectories.…”
Section: Protective Factors In the Face Of The Educational Exclusion ...mentioning
confidence: 96%
“…To best inform policies and practices targeting extrinsic protective factors in mental health promotion among AHS students, further research is needed to verify whether our findings regarding the lack of protective associations can be replicated or are an anomaly. Some existing studies suggest that measures of connectedness and social support may operate differently among AHS students (Griffiths et al, 2019;Johnson et al, 2014), warranting further in-depth exploration to understand why. For example, given the high level of ACEs experienced by AHS students, perhaps family relationships are not supportive, and AHS students rely more on nonfamilial adults for prosocial support and connection.…”
Section: Discussionmentioning
confidence: 99%